A Study of Pattern of Burn Injury at Civil Hospital Karachi (Medical Forum Monthly, 2024)
Objective: To determine pattern of diversified types of injury.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Medico-Legal Department, Civil Hospital Karachi from January 2012 to July 2015.Materials and Methods: The medico legal records of 3856 patients in the Burn Centre Civil Hospital Karachi were selected and collected. The data was reviewed under the consideration of type of burns, sex and fatality. The data was analyzed using SPSS version 16 and frequencies and percentages were obtained for variables according to the methodology.Results: In study of 3856 patients, majority of them sustained injury from fire burn, electrical burn, scars and chemical burn as 76.11% , 13.07%, 8.80%, 2.02% respectively. Male to female ratio of 1.58: 1.0 is observed in the study mold, showing a male domineering. The mortality rate was 37.73% with morbidity of 62.27%.Conclusion: Majority of burn victims were male who sustained injury from a fire burn as they are more exposed to external plunge in encompassment especially at work places in our society. An intensive program is needed to curtail and counter burn injuries along with further evaluation to achieve estimable results.